Literature Review: Hubungan Dukungan Suami dan Tenaga Kesehatan dengan Penggunaan Metode Kontrasepsi Jangka Panjang (MKJP) - Najibah Lestari; Meitria Syahadatina Noor; Ferry Armanza (Homeostasis, 2021)
Abstract: Long term contraceptive methods (LTCMs) are contraceptive methods can be used effective for a long period, and efficient to delaying pregnancy. LTCMs, users in Indonesia are classified as low, specifically 7,920,260 users (21,81%). The fact0rs that influence the use of LTCMs needs support from husbands, support from heaIth workers in using LTCMs. The purpose of this literature review is to explain the relationship between husband support and health workers with the use of LACMs. The method in this study uses a systematic literature review of 20 related research literature. The value showed that the percentage of literature related to the variable of husband's support with the use of LACMs was 61%, and the husband's support that was not related to the use of LACMs was 39%. While the value of the study showed that the percentage of literature related to the variable support for health workers with the use of LACMs was as much as 75% and the support for health personnel who were not related to the use of LACMs was 25%. Keywords: relationship, husband support, health worker support, long term contraceptive methods (LTCMs) Abstrak: Metode kontrasepsi jangka panjang (MKJP) adalah metode k0ntrasepsi yang masa kerjanya lama dan mempunyai efektivitas tinggi terhadap pencegahan kehamilan. Penggunaan MKJP di lndonesia tergolong sedikit sebesar 7.920.260 pengguna (21,81%). Faktor yang berpengaruh dalam MKJP yaitu dukungan suami dan dukungan tenaga kesehatan dalam penggunaan MKJP. Tujuan kajian literatur ini untuk menjelaskan hubungan dukungan suami dan tenaga kesehatan dengan penggunaan MKJP. Metode penelitian ini menggunakan systematic literature review terhadap sebanyak 20 litarature penelitian yang berkaitan. Hasil penelitian menunjukan persentase literature yang berhubungan untuk variabel dukungan suami dengan penggunaan MKJP sebanyak 61%, dan dukungan suami dengan penggunaan MKJP yang tidak berhubungan sebanyak 39%. Hasil penelitian menunjukan pesentase literature yang berhubungan untuk variabel dukungan tenaga kesehatan dengan penggunaan MKJP sebanyak 75% dan dukungan tenaga Kesehatan yang tidak berhubungan dengan penggunaan MKJP sebanyak 25%. Kata-kata kunci: hubungan, dukungan suami, dukungan tenaga kesehatan, MKJP